1999
DOI: 10.2113/gsecongeo.94.3.357
|View full text |Cite
|
Sign up to set email alerts
|

Regional oxygen isotope zonation at Broken Hill, New South Wales, Australia; large-scale fluid flow and implications for Pb-Zn-Ag mineralization

Abstract: Metasedimentary and metavolcanic rocks at Broken Hill, Australia, show regional-scale lowering of 8•sO values from as high as 16 per mil in Paragon Group metasedimentary rocks to values as low as 7 per mil within a few hundreds of meters of Pb-Zn-Ag orebodies. Such large-scale oxygen isotope resetting cannot be achieved by closed-system processes (such as partial melting or devolatization), implying that the rocks were affected by fluid flow. The preservation of peak metamorphic •sO fractionations between coex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 28 publications
2
6
2
Order By: Relevance
“…(2000) inferred a mixed reservoir of fluids for calcsilicate alteration sourced from the devolatilization of a rift related volcano‐sedimentary sequence and the intrusion of the regional S‐type granites during the later stages of the D3 event. This is in contrast to the findings of Cartwright (1999) who concluded that fluids involved in the resetting of δ 18 O values pre‐dated regional metamorphism and granite generation because of fluid‐absent partial melting occurring during peak regional metamorphism. Cartwright (1999) further suggests that lack of correlation between δ 18 O values and widespread retrograde metamorphic assemblages indicates it is unlikely that retrogression involved large volumes of accompanying fluid flow.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…(2000) inferred a mixed reservoir of fluids for calcsilicate alteration sourced from the devolatilization of a rift related volcano‐sedimentary sequence and the intrusion of the regional S‐type granites during the later stages of the D3 event. This is in contrast to the findings of Cartwright (1999) who concluded that fluids involved in the resetting of δ 18 O values pre‐dated regional metamorphism and granite generation because of fluid‐absent partial melting occurring during peak regional metamorphism. Cartwright (1999) further suggests that lack of correlation between δ 18 O values and widespread retrograde metamorphic assemblages indicates it is unlikely that retrogression involved large volumes of accompanying fluid flow.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies (Ashley, 2000; Skirrow & Ashley, 2000; Teale & Fanning, 2000) have focused on the isotopic signatures of and timing of fluid flow with respect to the mineralization in the region. Cartwright (1999) and Doyle & Cartwright (2000) have carried out an investigation of stable isotopic systematics of fluid flow in shear zones in the Broken Hill Domain, in relation to the Broken Hill Pb‐Zn‐Ag mineralization system. These studies have proposed a hybrid magmatic–metamorphic source of fluids with an either syn‐ or post‐orogenic timing for alteration.…”
Section: Geological Settingmentioning
confidence: 99%
“…8). A similar pattern also is observed in most VMSDs (Green et al, 1983;Ohmoto, 1996;Gemmell et al, 1998;Cartwright, 1999;Shikazono, 2003). Alteration of CZ2 rocks must have been produced by higher temperature fluids compared with those responsible for the alteration of rocks from the CZ1, which caused oxygen isotopic shifts toward lower values.…”
Section: Whole-rock Stable Isotope Constraints On the Paleohydrothermsupporting
confidence: 70%
“…The d 18 O halos are opposite those of most Archean and Phanerozic VMSDs, including Kuroko-type deposits, in which 18 O values decrease toward the mineralized zone and increase outward from this zone (Barrett and MacLean, 1994;Ohmoto, 1996;Vásquez et al, 1998;Gemmell et al, 1998;Cartwright, 1999;Shikazono, 2003). However, at the Kidd Creek VMSD, a reverse d 18 O pattern, similar to that of the Serra do Itaberaba Group, is observed at both a decimeter scale beneath the mineralization zone and a regional scale with higher whole-rock 18 O values near the mineralized zone.…”
Section: Whole-rock Stable Isotope Constraints On the Paleohydrothermmentioning
confidence: 99%
“…Interest in the ore-forming history of sedimentary rocks and basins has grown rapidly since 1960 and is now intensified ( Cartwright, 1999 ;Bechtel and Elliott, 1999 ;Raymond and Peter, 1999 ;Dooley and McClay, 1997) . The main reason behind the acceleration is the increasing awareness that the key factors responsible for the formation of metal deposits in a sedimentary basin are the source rocks beneath the basin and intensive hydrothermal activity in it .…”
Section: Introductionmentioning
confidence: 99%